The Role of Supervisory tools in Addressing Bank Borrowers' Currency Mismatches - Mendez Morales, Armando; Mar Cacha, Maria del. (Washington, D.C. : International Monetary Fund, 2003)
Bank borrowers' currency mismatches often result from unhedged foreign currency borrowing in economies where there is significant dollarization, exposing the financial sector to disguised credit risk. In the absence of standard tools or guidelines to counteract this risk, countries have resorted to outright regulatory limits in cases of moderate dollarization and to undesirable exchange controls in other cases. This paper proposes a "specific-to-group" provision rule based on the effective borrowing cost differential between domestic and foreign currency. Such a rule would help internalize the corresponding risks for banks and their borrowers in line with internationally accepted prudential and accounting standards.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet